해안지하수위가 해빈변형에 미치는 영향 - 이우동(Woo-Dong Lee); 허동수(Dong-Soo Hur) (Han-guk haeyang gonghak hoeji (Online), 2019)
In order to understand the characteristics of beach deformation, in this study, numerical simulations were conducted using a 3-D hydro-morphodynamic model (HYMO-WASS-3D) to analyze the characteristics of beach deformation due to the coastal groundwater levels. HYMO-WASS-3D directly analyzed the nonlinear interaction between the hydrodynamic and morphodynamic processes in the coastal area. The simulation results of HYMO-WASS-3D showed good agreement with the experimental results on the changes in the profile of the beach in the surf and swash zones. Then, numerical simulations were conducted to examine the characteristics of beach deformation due to the variation of the level of the coastal groundwater. As a result, the beach profiles were examined in relation to the wave breaking in the surf zone and the wave uprush and backwash in the swash zone due to the differences in the water levels. This paper also discussed the temporal and spatial distributions of the velocities, vorticities, and suspended sediments in the surf and swash zones with various levels of the coastal groundwater.